Gelsolin dysfunction causes photoreceptor loss in induced pluripotent cell and animal retinitis pigmentosa models - Roly Megaw (Nature Portfolio, 2017)
Mutations in the Retinitis Pigmentosa GTPase Regulator (RPGR) cause retinal dystrophy, but how this arises at a molecular level is unclear. Here, the authors show in induced pluripotent stem cells and mouse knockouts that RPGR mediates actin dynamics in photoreceptors via the actin-severing protein, gelsolin.